Sosialisasi Penanaman 2500 Bibit Pohon Bagi Masyakarakat Di Desa Harapan Maju Kecamatan Sei Lepan Kabupaten Langkat - Cici Arianti; Muhammad Farhan; Suci Rahmah; Enni Suhenni (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the steps that students can take to increase their sense of concern for the environment is by planting tree seedlings. The planting was carried out in Harapan Maju Village, Sei Lepan Kec. The location selection was based on the location of the KKN STAI-JM Tanjung Pura student service. The activity certainly has a positive impact on the surrounding environment so that the people of Harapan Maju Village, Sei Lepan Kec. can breathe fresh air again. The activity, which was carried out on March 30, 2023, involved Harapan Maju Village Officials and the Farmer Group Association (Gapoktan) as well as Bhabinkamtibmas of Pangkalan Brandan Police Harapan Maju Village by planting mangosteen, avocado, clove and jengkol trees which in total amounted to 2500 tree seedlings. The responsibility for the maintenance of these plants is a shared responsibility between the students and the entire community of Harapan Maju Village, Sei Lepan Sub-district. This activity is expected to increase the awareness of the people of Harapan Maju Village, Sei Lepan Sub-District on the importance of maintaining and preserving trees, especially in Harapan Maju Village, Sei Lepan Sub-District.